Politics, Violence, Memory : The New Social Science of the Holocaust - Welch, Susan; Subotic, Jelena; Kopstein, Jeffrey (Book collections on Project MUSE., 2023)
"This book highlights important new social scientific research on the Holocaust and initiates the integration of the Holocaust into mainstream social scientific research in a way that will be useful both for social scientists and historians"--